GWAS‐based pathway analysis differentiates between fluid and crystallized intelligence. (8th August 2014) - Christoforou, A.; Espeseth, T.; Davies, G.; Fernandes, C. P. D.; Giddaluru, S.; Mattheisen, M.; Tenesa, A.; Harris, S. E.; Liewald, D. C.; Payton, A.; Ollier, W.; Horan, M.; et al.
Abstract : Cognitive abilities vary among people. About 40–50% of this variability is due to general intelligence ( g ), which reflects the positive correlation among individuals' scores on diverse cognitive ability tests. g is positively correlated with many life outcomes, such as education, occupational status and health, motivating the investigation of its underlying biology. In psychometric research, a distinction is made between general fluid intelligence ( g F) – the ability to reason in novel situations – and general crystallized intelligence ( g C) – the ability to apply acquired knowledge. This distinction is supported by developmental and cognitive neuroscience studies. Classical epidemiological studies and recent genome‐wide association studies (GWASs) have established that these cognitive traits have a large genetic component. However, no robust genetic associations have been published thus far due largely to the known polygenic nature of these traits and insufficient sample sizes. Here, using two GWAS datasets, in which the polygenicity of g F and g C traits was previously confirmed, a gene‐ and pathway‐based approach was undertaken with the aim of characterizing and differentiating their genetic architecture. Pathway analysis, using genes selected on the basis of relaxed criteria, revealed notable differences between these two traits. g F appeared to be characterized by genes affecting the quantity and quality of neurons and therefore neuronal efficiency, whereas long‐term depression (LTD) seemed to underlie g C. Thus, this study supports the g F– g C distinction at the genetic level and identifies functional annotations and pathways worthy of further investigation. Abstract : GWAS‐based pathway analysis differentiates between fluid and crystallized intelligence ( g F and g C).